Impact of eating and drinking on body composition measurements by bioelectrical impedance. Issue 2 (26th August 2014) - Androutsos, O.; Gerasimidis, K.; Karanikolou, A.; Reilly, J. J.; Edwards, C. A.
Abstract: Background: Bioelectrical impedance analysis would be a more practical tool to measure body composition in clinical settings, dietetic practice and epidemiological studies if patients/subjects did not have to fast before measurements. The present study assessed whether the ingestion of food or drink had any biologically significant effect on bioimpedance measurements and body composition by the foot‐to‐foot method. Methods: Fifty‐five healthy adults [30 males and 25 females; mean (SD) age 27.7 (7.1) years; mean (SD)body mass index 24 (3.8) kg m −2 ] were randomly assigned to a 2‐day food trial (high‐fat meal or high‐carbohydrate meal) or a 2‐day drink trial (water or high electrolyte drink). Body composition measurements were carried out in the fasting state, immediately after meal consumption and every 30 min for 2 h by the foot‐to‐foot single frequency bioimpedance technique. Results: Bioimpedance increased significantly after the ingestion of food and fluid, although the changes were small. The electrolyte drink, high‐fat and high‐carbohydrate meals significantly increased the percentage body fat and fat mass. In all cases, the median percentage changes from baseline were approximately 1% in body fat percentage units. Conclusions: Although there were statistically significant changes in body composition estimates after food or drink consumption, these were small and within the imprecision of the impedance technique, and so are unlikely to be of clinical significance. The present study suggests that impedance measures of body fatness in clinical settings do not require strict adherence to fasting, and this should increase the opportunities for clinical application.